2010
DOI: 10.1051/0004-6361/201015065
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an updated14N(p,γ)15O reaction rate on advanced evolutionary stages of low-mass stellar models

Abstract: We investigate the impact of the 14 N(p, γ) 15 O reaction rate as redetermined by the LUNA experiment, on the shell H-burning and core He-burning phases of low-mass, metal-poor stellar models. The new reaction rate has small but noticeable effects, the largest one being a ∼7−8% reduction in the red giant branch lifetimes. To different degrees, the lifetimes and luminosities of horizontal branch models, the mass of the stellar models evolving within the RR Lyrae instability strip, the luminosity of the red gian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…More specifically, for this comparison the PGPUC SEC uses the F04 rate, whereas BaSTI uses the NACRE one. Pietrinferni et al (2010) pointed out that two ZAHB loci created with these rates have a difference in luminosity of the order presented here at log T eff = 3.85, the ZAHB determined with the NACRE reaction rate being brighter (at this metallicity). As far as the predicted temperatures are concerned, we do not find any significant differences.…”
Section: Comparison With Other Codesmentioning
confidence: 51%
“…More specifically, for this comparison the PGPUC SEC uses the F04 rate, whereas BaSTI uses the NACRE one. Pietrinferni et al (2010) pointed out that two ZAHB loci created with these rates have a difference in luminosity of the order presented here at log T eff = 3.85, the ZAHB determined with the NACRE reaction rate being brighter (at this metallicity). As far as the predicted temperatures are concerned, we do not find any significant differences.…”
Section: Comparison With Other Codesmentioning
confidence: 51%
“…Pietrinferni et al (2010) found that the LUNA reaction rate leads to a larger value for M He c , of the order of ≈ 0.002 − 0.003M ⊙ , with respect to the results obtained by using the NACRE rate. Despite the larger He core mass of the models based on the LUNA rate, their TRGB brightness is lower by about ∆ log(L TRGB /L ⊙ ) = 0.02.…”
Section: Nuclear Reaction Ratesmentioning
confidence: 59%
“…The impact of the LUNA rate on the He core mass and brightness at the RGB tip of low-mass stars has been investigated by Weiss et al (2005) and Pietrinferni et al (2010). Pietrinferni et al (2010) found that the LUNA reaction rate leads to a larger value for M He c , of the order of ≈ 0.002 − 0.003M ⊙ , with respect to the results obtained by using the NACRE rate.…”
Section: Nuclear Reaction Ratesmentioning
confidence: 99%
“…Note that revisions to energetically important reaction rates can have a significant impact on stellar ages. Revisions of the 14 N(p, γ) 15 O rate by Formicola et al (2004) led to an increase in the predicted age of the oldest globular clusters , in addition to altering the lifetimes and luminosities of advanced evolutionary phases of low-mass stars (Pietrinferni et al 2010). When utilising a given set of tracks, one should always check that the reaction rates used are up-to-date.…”
Section: Discussionmentioning
confidence: 99%